Soybean aphid biotype 1 genome: Insights into the invasive biology and adaptive evolution of a major agricultural pest. (May 2020) - Giordano, Rosanna; Donthu, Ravi Kiran; Zimin, Aleksey V.; Julca Chavez, Irene Consuelo; Gabaldon, Toni; van Munster, Manuella; Hon, Lawrence; Hall, Richard; Badger, Jonathan H.; Nguyen, Minh; Flores, Alejandra; Potter, Bruce; et al.
Abstract: The soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae) is a serious pest of the soybean plant, Glycine max, a major world-wide agricultural crop. We assembled a de novo genome sequence of Ap. glycines Biotype 1, from a culture established shortly after this species invaded North America. 20.4% of the Ap. glycines proteome is duplicated. These in-paralogs are enriched with Gene Ontology (GO) categories mostly related to apoptosis, a possible adaptation to plant chemistry and other environmental stressors. Approximately one-third of these genes show parallel duplication in other aphids. But Ap. gossypii, its closest related species, has the lowest number of these duplicated genes. An Illumina GoldenGate assay of 2380 SNPs was used to determine the world-wide population structure of Ap. Glycines. China and South Korean aphids are the closest to those in North America. China is the likely origin of other Asian aphid populations. The most distantly related aphids to those in North America are from Australia. The diversity of Ap. glycines in North America has decreased over time since its arrival. The genetic diversity of Ap. glycines North American population sampled shortly after its first detection in 2001 up to 2012 does not appear to correlate with geography. However, aphids collected on soybean Rag experimental varieties in Minnesota (MN), Iowa (IA), and Wisconsin (WI), closer to high density Rhamnus cathartica stands, appear to have higher capacity to colonize resistant soybean plants than aphids sampled in Ohio (OH), North Dakota (ND), and South Dakota (SD). Samples from the former states have SNP alleles with high F ST values and frequencies, that overlap with genes involved in iron metabolism, a crucial metabolic pathway that may be affected by the Rag -associated soybean plant response. The Ap. glycines Biotype 1 genome will provide needed information for future analyses of mechanisms of aphid virulence and pesticide resistance as well as facilitate comparative analyses between aphids with differing natural history and host plant range. Graphical abstract: Image 1 Highlights: Draft genome of Aphis glycines B1, a culture established in 2001, the first year subsequent to its discovery in the U.S. The duplicated proteome of Ap. glycines contains genes involved in apoptosis, possible adaptation to plant chemical defenses. SNP based population analysis indicates China and South Korea as likely sources of invasive U.S. soybean aphid population. Ap. glycines genetic diversity in North America has decreased over the sampled time period. Unlike aphids on susceptible plants, those on Rag in MN, IA, WI but not OH, ND, SD show high rate of iron metabolism alleles.